Witchcraft as metaculture in the Bolivian Chaco - Kathleen Lowrey (Journal de la Société des Américanistes)
Witchcraft as metaculture in the Bolivian Chaco. This paper treats a multi-village assembly that was held to adjudicate an accusation of witchcraft in the Guaraní-speaking indigenous community of Isoso, in the Bolivian Chaco, in 1999. The argument of the article is that the leadership of this community attempted an anthropological treatment of a problem of witchcraft by addressing it at a « meta-cultural » level having to do with community dynamics. However, the Isoseño leadership found – as have anthropologists – that shifting the frame of reference of a problem is not the same as resolving it, and that conflict can be as easily transmuted as can frames of analysis. The article concludes that a sophisticated, reflexive self-consciousness about culture on the part of modern indigenous leaders may not allow them to transcend culture in their home communities, any more than the culture concept has allowed anthropologists to solve their most puzzling disciplinary problems.